Interactive Videos Enhance Learning about Socio-Ecological Systems. Issue 1 (2nd January 2018) - Smithwick, Erica; Baxter, Emily; Kim, Kyung; Edel-Malizia, Stephanie; Rocco, Stevie; Blackstock, Dean
Abstract: Two forms of interactive video were assessed in an online course focused on conservation. The hypothesis was that interactive video enhances student perceptions about learning and improves mental models of social-ecological systems. Results showed that students reported greater learning and attitudes toward the subject following interactive video. Moreover, metrics of network complexity applied to students' concept maps of socio-ecological systems increased longitudinally through the course highlighting greater awareness of socio-ecological linkages. We conclude that interactive video can increase awareness of interdisciplinary connections in socio-ecological systems and should be more widely employed in general education geography courses.